2013
DOI: 10.1519/jsc.0b013e31828b8e4c
|View full text |Cite
|
Sign up to set email alerts
|

More Complicated Than it Looks

Abstract: Activities thought to induce high intra-abdominal pressure (IAP), such as lifting weights, are restricted in women with pelvic floor disorders. Standardized procedures to assess IAP during activity are lacking and typically only focus on maximal IAP, variably defined. Our intent in this methods paper is to establish the best strategies for calculating maximal IAP and to add area under the curve and first moment of the area as potentially useful measures in understanding biologic effects of IAP. Thirteen women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We approximated the power of a mixed model analysis of variance, with multiple comparisons of 5 lifting activities versus this reference activity, using formulae for Sidak corrected t-tests at the 1% significance level, adjusted for intra-woman clustering assuming an ICC = 0.45. Based on our preliminary data in which the net (that is, the difference between maximal and minimal IAP during a specific activity [12]) mean maximal IAP for lift-and-carry was (35.2 cm H 2 0, SD 9.3), this calculation indicated that a sample size of 46 women would provide approximately 80% power to detect a difference of 20 cm H 2 0 (ie, net mean IAP of 30 vs 50 cm H 2 0 or total mean IAP of 50 vs 70 cm H 2 0) in the comparison of one lifting activity versus the control. Therefore we planned to enroll up to 60 women to obtain a final complete dataset for 46.…”
Section: Methodsmentioning
confidence: 99%
“…We approximated the power of a mixed model analysis of variance, with multiple comparisons of 5 lifting activities versus this reference activity, using formulae for Sidak corrected t-tests at the 1% significance level, adjusted for intra-woman clustering assuming an ICC = 0.45. Based on our preliminary data in which the net (that is, the difference between maximal and minimal IAP during a specific activity [12]) mean maximal IAP for lift-and-carry was (35.2 cm H 2 0, SD 9.3), this calculation indicated that a sample size of 46 women would provide approximately 80% power to detect a difference of 20 cm H 2 0 (ie, net mean IAP of 30 vs 50 cm H 2 0 or total mean IAP of 50 vs 70 cm H 2 0) in the comparison of one lifting activity versus the control. Therefore we planned to enroll up to 60 women to obtain a final complete dataset for 46.…”
Section: Methodsmentioning
confidence: 99%
“…Descriptions of how maximal intra-abdominal pressure is calculated vary or are absent from literature to date. We have described standardised methods for assessing maximal pressure during physical activity (Hamad et al, 2013). However, other qualities of intra-abdominal pressure besides maximal pressure may also be relevant to understanding the impact of strenuous activities on conditions such as pelvic floor disorders.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Figure 4, this AUC is greater than that for the Mat and Reformer Pilates sessions combined. Area under the curve measurements describing IAP are used very little in the literature [23, 27]. However, AUC is commonly used in endocrinological and neuroscience research to reflect information that is contained in repeated measures over time, and in pharmacology to determine the effects of medication over a time period or to evaluate dose and response relationships [28].…”
Section: Discussionmentioning
confidence: 99%
“…A custom Matlab software (R2011A, MathWorks) program was used to evaluate the pressure data as previously described [23]. Maximal IAP was calculated by averaging the 10 maximal peaks in the waveform each separated by one second.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation